The Modern(?) Korean Woman in Prime-Time: Analyzing the Representation of Sun on the Television Series Lost. - MEYER, MICHAELAD.E.; STERN, DANIELLEM. (Women's Studies)
This article investigates the representation of Sun, the most prominent non-white female character on ABC's Lost. Given the importance of Sun's character in terms of visibility for Korean women specifically (and Asian women generally) coupled with the fact that Lost under-represents women in general, her role provides a substantial case-study of gender within the science fiction genre. Through a narrative analysis of the first season, we demonstrate the simultaneously flawed and empowered dimensions of Sun, who challenges some of the stereotypes viewers have come to expect from prime-time drama. Elements of colonialism, interpersonal relationships, and the castaway narrative in Lost are also explored.